2022
DOI: 10.3390/info13020059
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive Classification of Blood Glucose Level for Early Detection Diabetes Based on Photoplethysmography Signal

Abstract: Monitoring systems for the early detection of diabetes are essential to avoid potential expensive medical costs. Currently, only invasive monitoring methods are commercially available. These methods have significant disadvantages as patients experience discomfort while obtaining blood samples. A non-invasive method of blood glucose level (BGL) monitoring that is painless and low-cost would address the limitations of invasive techniques. Photoplethysmography (PPG) collects a signal from a finger sensor using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 43 publications
(62 reference statements)
0
11
0
1
Order By: Relevance
“…Figure 6 shows that for all the subjects, the PPG cycles were found to have higher amplitudes and narrower peaks during low glucose periods. Based on this observation and the available literature [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 29 , 30 , 31 ], we created features that capture this change in the dynamics at different glucose levels, as shown in Figure 7 . In addition to these features, the energy profile of each cycle was calculated using the Teager–Kaiser energy operator (TKEO), a feature commonly used to quantify the instantaneous energy profile in periodic components of signals [ 15 , 16 , 17 , 18 ].…”
Section: Signal Processing/methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 6 shows that for all the subjects, the PPG cycles were found to have higher amplitudes and narrower peaks during low glucose periods. Based on this observation and the available literature [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 29 , 30 , 31 ], we created features that capture this change in the dynamics at different glucose levels, as shown in Figure 7 . In addition to these features, the energy profile of each cycle was calculated using the Teager–Kaiser energy operator (TKEO), a feature commonly used to quantify the instantaneous energy profile in periodic components of signals [ 15 , 16 , 17 , 18 ].…”
Section: Signal Processing/methodsmentioning
confidence: 99%
“…The principle of PPG is that blood with a higher concentration of glucose will have different absorbance than blood with lower glucose levels. This will affect the shape of the PPG signal which can then be used to indirectly estimate the blood glucose level through a mapping onto a set of features that are fed into the machine learning algorithms [ 12 , 13 , 14 , 15 , 17 , 18 , 29 ].…”
Section: Materials and Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study demonstrated the application of a PPG device in the classification of blood glucose levels into normal and diabetic ( Susana et al, 2022 ). With PPG signal and blood glucose data collected from 80 participants, the study reported an accuracy of 98% with a decision tree based classifier.…”
Section: Non-invasive Sensors and Wearablesmentioning
confidence: 99%
“…Microwave filters or antennas are employed for monitoring glucose levels in the blood [24][25]. This is a non-invasive technology that has been developed.…”
Section: Introductionmentioning
confidence: 99%